2020
DOI: 10.21101/cejph.a5730
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence and prevalence of cardiovascular risk factors and evaluation of their control in epidemiological survey in the Czech Republic

Abstract: Objective: The aim of this analysis was to analyze the presence of the most important cardiovascular (CV) risk factors and to discuss patterns of LDL cholesterol management in the population studied. Methods: We enrolled 961 males, average age of 42.9 ± 4.7, and 851 females, average age of 51.2 ± 3.6. Data on personal, pharmacological and family history, and laboratory examinations were collected. Cardiovascular (CV) risk was calculated using the Systematic Coronary Risk Evaluation (SCORE) algorithm with modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Similarly, longitudinal population data from the Czech Republic showed that statins were the most commonly prescribed regimen, with 79% of patients receiving statins in recent years [28]. Despite the availability of statins, recently published studies focusing on individual countries in CEE have highlighted the significant burden of dyslipidaemia in this region and the need for further action to achieve optimal LDL-C levels in CEE [29][30][31][32][33]. The LIPIDOGRAM studies are the largest population-based surveys assessing the prevalence of dyslipidaemia in Poland, which demonstrated that the number of patients with dyslipidaemia in Poland remains high [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, longitudinal population data from the Czech Republic showed that statins were the most commonly prescribed regimen, with 79% of patients receiving statins in recent years [28]. Despite the availability of statins, recently published studies focusing on individual countries in CEE have highlighted the significant burden of dyslipidaemia in this region and the need for further action to achieve optimal LDL-C levels in CEE [29][30][31][32][33]. The LIPIDOGRAM studies are the largest population-based surveys assessing the prevalence of dyslipidaemia in Poland, which demonstrated that the number of patients with dyslipidaemia in Poland remains high [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Of 13,724 Polish primary care patients enrolled in the LIPIDOGRAM2015 study, over 80% had dyslipidaemia, more than 60% had hypertension and more than 75% patients were overweight or obese [32]. Similarly, a cross-sectional study of men and women from the primary care setting in Czech Republic showed a very high prevalence of dyslipidaemia (39% and 41%, respectively) [33]. Other contemporary population-based and cross-sectional studies have also included countries in CEE in their analyses and have highlighted the unmet need within this population [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination of information about the importance and need to prevent cardiovascular disease in overweight people, in addition to being a process that does not require sophisticated technology, only control, lifestyle changes, self-knowledge and self-management of the body and health, yet is one of the most effective measures, as it is able to raise awareness about their behavior mediated by beliefs, culture, habits and individual and collective knowledge that mediate decision-making, making them one of the most responsible for compromising their health and wellbeing [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Согласно данным американского популяционного исследования с поправкой на пол и возраст, распространенность СД колеблется от 12,1% среди белых неиспанцев до 22,1% среди афроамериканцев [14]. В чешском исследовании было выявлено, что частота СД среди взрослой популяции мужчин и женщин сопоставимая и составляет 11% [12].…”
Section: Discussionunclassified